Pengaruh Etika Auditor, Pengalaman Kerja dan Kompetensi Terhadap Kualitas Audit Pada BPKP Provinsi Sumatera Selatan - Muhammad Pramudya Antasari; Rita Martini; Eka Jumarni Fithri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
A quality review can be utilized to discover out infringement within the bookkeeping framework used by the client. To attain this, the information and competence of an evaluator are required. This study analyzes evaluator morals, work involvement and competence. The most objective of this ponder is to analyze how evaluator morals, work involvement, and competence influence the quality of reviews conducted by the Budgetary and Improvement Supervisory Office (BPKP) in South Sumatra Territory. The information utilized in this think about were gotten through surveys dispersed to 50 inspectors as respondents. In information investigation, different direct relapse investigation procedures were utilized with the assistance of the SPSS 25 program to test the theory. The test comes about appeared that reviewer morals had a positive and signitificant impact on review quality. Moreover, inspector work involvement and competence were moreover demonstrated to have a positive and signitificant impact on review quality. In expansion, at the same time, the three factors of inspector morals, work encounter, and competence together gave a positive and signitificant impact on the quality of the review created.